Perilaku Dan Pengalaman Beragama Remaja Jalanan: Tinjauan Psikologi Agama Dari Aspek Mental, Pemikiran, Dan Perilaku - Liyana Maulida Najibah; Noor Azidah Batubara; Cecep Suherman; Wulan Cahya Rizki; Siti Mahmudah; Ida Royani (JURNAL ILMIAH NUSANTARA, 2026)
This research aims to deeply understand the dynamics of religious behavior and experiences among street teenagers in the traffic light area near SGC Mall Cikarang. The main focus of the study covers three aspects: mental (inner well-being and spiritual experiences), cognitive (religious beliefs and views), and behavioral (daily religious practices). This study uses a descriptive qualitative approach through in-depth interviews and field observations. The findings reveal that the religiosity of street teenagers remains strong despite social and economic limitations. Their religious expression is reflected not only in worship practices but also in moral behavior and solidarity with one another. Religion serves as a source of meaning, peace, and mental strength in facing the harsh realities of street life.